Две взятки на мизере: роман / Диля Еникеева - Еникеева Диля Дэрдовна (Женщины могут все, 2002)
Экземпляры: ф.22 (2003) / Инвентарный номер: 47575 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: Е 63 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44